(untitled) (Medical Forum Monthly, 2024)
Objectives: To see whether the cortex of mandible on an OPG can be employed for early detection and screening tool for osteoporosis. Study Design: Cross sectional study. Place and Duration of Study: The study was conducted in IBMS, DUHS Karachi and stretched over a period of eight months from December 2011 to July 2012. Materials and Methods: One hundred and seventy four female subjects, aged 25 to 85 years, were divided into premenopausal (Group I) and postmenopausal (Group II) groups. Each group was subdivided into normal (pre A, post A), osteopenic (pre B, post B) and osteoporotic (pre C, post C) groups by Dual Energy X- ray Absorptiometry (DXA) Scan. Mandibular morphological changes seen on OPG in subgroups of Group I were compared with each other and with subgroups of Group II. Cortical thickness at mental foramen (CMF) was observed on OPG. Statistical analysis was performed by SPSS version 16 using One Way Analysis Of Variance (ANOVA) to evaluate intra group significance and for intergroup significance independent samples T-test was applied. Results: The thickness of Mandibular cortex at mental foramen (CMF) was found to be significantly decreased in osteoporotic patients. Conclusion: In conclusion a simple method of screening was established which can be used as early detector of osteoporosis in a cost effective manner.